Penerapan Model Teams Games Tournament untuk Meningkatkan Hasil Belajar Kelas V SDN 36 Parepare - Usman Usman; Nur Ilmi; Idza Sri Anugrah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine the application of a cooperative learning model of the teams games tournament type can improve the learning process and learning outcomes. This research method uses a qualitative research approach and the type of research used is the type of Classroom Action Research (PTK). The subjects in this study were class V students of UPTD SDN 36 Parepare 2022/2023 school year, totaling 20 students consisting of 14 men and 6 women, as well as a teacher. The focus of this study is the process focus and focus on student learning outcomes about human interaction with the environment by applying a teams games tournament type cooperative learning model. The data collection techniques used are observation, tests, and documentation. The data analysis techniques used are data condensation, data presentation and drawing qualitatively processed conclusions. Based on the research conducted, the results obtained for cycle I are in the Sufficient category (C) and for cycle II are in category (B). The conclusion in this study is that the process and results of student learning about human interaction with the environment in class V UPTD SDN 36 Parepare by applying a cooperative learning model type of teams games tournament has increased.